PENENTUAN KADAR FLAVONOID DARI EKSTRAK KULIT SALAK (Salacca zalacca. Reinw) BERDASARKAN PERBEDAAN PENGERINGAN SIMPLISIA - Robbiyan Robbiyan; Mauritz Marpaung Pandapotan; Riza Apriani (Lantanida Journal, 2021)
The skin of the thorny palm has been empirically recognized by some people as a traditional medicine for beauty, antimicrobial, and antidiabetic. Compounds that act as treatment in the skin of the thorny palm is flavonoids. The study aims to determine the total flavonoid of the thorny palm rind extract based on differences in the drying of simplicia. The simplicia drying method used was oven-dry, direct sunlight, indirect sunlight, and air dry and fresh samples as control. Extraction using the maceration method with ethanol p.a. solvent. Determination of total flavonoid levels from the extract of thorny palm rind using the UV-Vis spectrophotometric method with quercetin standard solution. The qualitative test results showed that the skin of the thorny palm contains flavonoids after the addition of 1% AlCl3. The total flavonoid content in the fresh sample was 0.00342%, direct sunlight was 0.00350%, oven-dry was 0.00340%, dry air was 0.00357%, and indirect sunlight was 0.00361%. Therefore, it can be concluded that the highest flavonoid content in the extract of thorny palm rind is found in the indirect sun drying method.